Fuzzy control and co-simulation for semi-active suspension based on improved genetic algorithm. (1st January 2013) - Zhang, Jingjun; Xu, Zhiqiang; Gao, Ruizhen
A vehicle semi-active suspension is established by using Adams software. The fuzzy logic controller of the suspension is completed from the Matlab software, and the control rules are optimised using improved genetic algorithm. And then using Adams/control module has realised the co-simulation of Adams and MATLAB. The results illustrate that this control method has decreased the body's acceleration to a large extent and improved vehicle's riding performances than the passive suspension. At the same time, the results also verify the feasibility and accuracy of using co-simulation.